Sexual health clinics for women led by specialist nurses or senior house officers in a central London GUM service: a randomised controlled trial. Issue 2 (1st April 2002) - Miles, K; Penny, N; Mercey, D; Power, R
Abstract : Objectives: To assess the care process and clinical outcomes for two different models of GUM clinic for women: one led by specialist nurses and the other by senior house officers (SHOs) Method: An open randomised controlled trial was carried out in a central London genitourinary medicine (GUM) women's clinic. Of 1172 women telephoning for an appointment, 880 were randomised to provide 169 eligible patients in the specialist nurse arm and 178 in the SHO arm. Of the eligible patients a total of 224 attended their appointment. The clinical records of the randomised women were audited for adequacy of care according to local guidelines. 30 key variables were objectively assessed and recorded on a standard audit form. An overall unitary index score (%) was calculated for each patient. The main variables associated with the outcome of specialist nurse and SHO decision making (diagnostic test request, preliminary diagnosis, and treatment provided) were then analysed independently. Results: The median documentation audit scores for specialist nurses (n=103) and SHOs (n=121) were 92% and 85% respectively (p<0.0001). The specialist nurses' documentation was significantly (p<0.05) more complete than the SHOs' for five variables: details of menstrual cycle, physical examination, medication instructions given to patients, health promotion discussion, and provision of condoms. Specialist nurses performed equally to the SHOs with regard to requesting the correct diagnostic tests, providing the correct preliminary diagnosis, and providing the correct treatment. Conclusions: A model of care using trained GUM nurses working within agreed protocols can provide comprehensive patient care for female patients that is equal to care provided by SHOs. Our results raise important issues regarding advanced GUM nursing education and training, protocol development, and accountability.